Biofertilizer Effect on Growth, Protein and Carbohydrate Content in Stevia rebaudiana Var Bertoni - Patil, N.M. (Recent Research in Science and Technology, 2010)
A comparative study on effect of chemical fertilizers and bio-fertilizers was done on growth and biochemical parameters in Stevia rebaudiana Var Bertoni. The results indicated that chemical treatment increased plant growth when compared to control. Vermicompost treatment increased growth compared to control but not as much as observed in combination of organic and inorganic treatment . However a combination treatment of biofertilizer and chemical fertilizer increased chlorophyll, growth, carbohydrates and proteins content compared to control.. Therefore, it is necessary to evaluate and develop a balanced fertilization strategy that combines the use of chemical, organic or biofertilizer.